Conclusive determination of ethynyl radical hydrogen abstraction energetics and kinetics*. (17th October 2020) - Bowman, Michael C.; Burke, Alexandra D.; Turney, Justin M.; Schaefer III, Henry F.
Abstract : The ethynyl radical (C 2 H) is ubiquitous, appearing in a variety of environments from interstellar space to oxy-acetylene flames. Under these diverse conditions, ethynyl has a high affinity to abstract hydrogen atoms from nearby molecules. In this study, C 2 H + HX → C 2 H 2 + X, X = CH 3, NH 2, OH, F, PH 2, SH, Cl, C 2 H, CN, and NC reactions have been examined at a rigorously high level of theory. Various additive corrections have been appended to the coupled-cluster framework to converge the relative enthalpy of stationary points on the C 2 H + HX surfaces to subchemical accuracy (≤0.5 kcal mol − 1 ). The barriers for the abstraction of a hydrogen from NH 3, PH 3, and H 2 S are submerged below the relative enthalpy of their reactant asymptotes by 2.75, 2.48, and 1.39 kcal mol − 1, respectively. Abstractions from H 2, CH 4, H 2 O, and HCl are predicted to have moderate barriers to the abstraction of 2.64, 0.77, 3.82, and 2.19 kcal mol − 1, respectively, suggesting these reactions will be significant to various systems at moderate to high temperatures. Accurate kinetics were obtained for the C 2 H + H 2, CH 4, NH 3, and H 2 O reactions over a wide range of temperatures with excellent agreement to present experimental rate constants. GRAPHICAL ABSTRACT: